Spy school blackout - Gibbs, Stuart, 1969- (New York : Simon and Schuster Books for Young Readers, 2025)
"On their latest mission to save the world, Ben and his friends face a conniving villain, assassins, pirates, sharks, and very big lizards in the most remote -- and deadly -- location of any spy school yet!" --
Emergency procedures -- Archaeology -- Birthday cake -- Cybercrime -- Arrival -- Targeting -- Deduction -- Admission -- Dragons -- Evasive action -- Nautical maneuvers -- Amphibious assault -- Investigation -- Interrogation -- Piracy -- Siege
Map on endpapers.
Ages 8-12.
Grades 3-7.
Keywords: Spies -- Juvenile fiction; Middle school students -- Juvenile fiction; Computer crimes -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Schools -- Juvenile fiction; Indonesia -- Juvenile fiction; Spy fiction; Novels; Action and adventure fiction